(untitled) (Revista Argentina de Cirugía, 2022)
Metástasis to the breast from extramammary solid neoplasms is a very unusual condition. It must be clearly distinguished from primary carcinoma of the gland because of its different treatment and prognosis. Metastasis from renal carcinoma to the breast is even more rare. We herein report a case of a 57 years old woman, with a metastasis to the breast of a previously treated clear cell renal carcinoma.